KONCI JANUARI (Suatu Kajian PAK Di Negeri Tomalehu-Timur) - Sors Randi Selano (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2019)
The aim of the research is to study the konci januari tradition with a study of PAK. Konci januari tradition is one of the traditions that contains values and norms that function to regulate and direct the behavior of individuals and groups in the Tomalehu-East society, these values include the values of solidarity, fellowship, religion, education and respect . Tradition in general is a call, habit and law that places and controls behavior and relationships within the community. While specifically adat is a habit or way of life that has been passed down from the ancestors, this research was conducted with a qualitative research Mapproach. In Tomalehu-Timur country, Manipa Island sub-district with a population of 67 kk and a total of 287 people, consisting of 148 men and 139 women. Christian religious education according to Calvin is fertilizing the minds of believers and their children with the words below the guidance of the holy spirit through a number of learning experiences carried out by the church. So that in themselves produced continuous spiritual growth that is endorsed more deeply through self-service to God the Father of Jesus Christ in the form of acts of love towards each other. Relations or relations that existed after the 1999 conflict between Tomalehu-Timur State and other lands in the Manipa Islands sub-district were considered to be very good up to now due to the frequent activities that involved all elements of both the State staff and traditional figures and religious figures.Keyword: Konci Januari tradition, PAK Values